Biological aspects of Harmonia axyridis in comparison with Cycloneda sanguinea and Hippodamia convergens - Santos, Laís da Conceição dos; Santos-Cividanes, Terezinha Monteiro dos; Cividanes, Francisco Jorge; Matos, Sidnéia Terezinha Soares de (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the development, survival, reproductive capacity, and longevity of the Asian ladybug Harmonia axyridis in comparison with Cycloneda sanguinea and Hippodamia convergens. Coccinellid larvae and adults were fed daily with Schizaphis graminum. Ten couples of each species were isolated for evaluation of the adult phase. The duration of the larval stage of H. axyridis is the longest (10.2 days) and its adults are the heaviest (29.7 mg) compared with C. sanguinea and H. convergens. The three species showed similar percentages of survival during the developmental stages. An average of 82% of C. sanguinea, H. axyridis, and H. convergens larvae reached adulthood, which indicates that temperature (25°C) and the offered prey are favorable to coccinellid development. Harmonia axyridis produces a higher total number of eggs per female (1,029.2) than the other evaluated species. However, H. axyridis, which lives for an average of 147.2 days, does not show a significantly greater longevity than C. sanguinea (87.2 days) and H. convergens (134.3 days).
Keywords: biological control; coccinellid; development; longevity; ladybug; predator